Term Farh dalam Al-Qur'an - Syayfi, Shohib; Mu'tashim, Imam (Sekolah Tinggi Ilmu Ushuluddin Wadi Mubarak Bogor, 2021)
Many humans are confused in understanding happiness so that many of them lead an unbalanced life. In the Qur'an itself Allah also discusses the word happiness as a solution for humans. Like the words falāḥ, fauzan, faroḥa, sa'ādah. Meanwhile, the aim of this research is to describe the interpretation of farḥ meanings according to Ibnul Qayyim. The focus and core of this research is to identify the verses that mention the word farḥ in the Qur'an and describe the interpretation of Ibnul Qayyim in his commentary book. This type of research uses the method of literature review. As an approach, the author uses a thematic interpretation approach, this type of thematic study specifically examines certain terms in the Qur'an. The results of this study are that the authors found (1) there are far lafadz in the Qur'an that have been mentioned 22 times with various derivations (2) All of the far lafadz that have been mentioned all contain two elements of meaning. First, farḥ which contains a commendable meaning, namely the joy and pride of believers with His gifts and graces. Second, farḥ which contains a despicable meaning, namely the joy and arrogance of the disbelievers and hypocrites. Abstrak Banyak manusia yang rancu dalam memahami sebuah kebahagiaan sehingga banyak dari dari manusia yang menjalani hidup tidak seimbang. Dalam Al-Qur’an sendiri Allah juga membahas kata kebahagiaan sebagai jalan solusi bagi manusia. Seperti kata falāḥ, fauzan, faroḥa, sa’ādah. Sedangkan Salah tujuan penelitian ini adalah untuk menjabarkan penafsiran makna-makna farḥ menurut Ibnul Qayyim. Fokus dan inti penelitian ini adalah mengidentifikasi ayat-ayat yang menyebutkan kata farḥ dalam Al-Qur’an dan memaparkan penafsiran Ibnul Qayyim dalam kitab tafsirnya. Jenis penelitian ini menggunakan metode telaah pustaka. Sebagai pendekatannya, penulis menggunakan pendekatan tafsir tematik, jenis kajian tematik ini secara khusus meneliti term tertentu dalam Al-Qur’an. Hasil dari penelitian ini bahwa penulis menemukan (1) terdapat lafadz farḥ dalam Al-Qur’an telah disebutkan sebanyak 22 kali dengan berbagai derivasinya (2) Semua lafadz-lafadz farḥ yang telah disebutkan semuanya mengandung dua unsur makna. Pertama, farḥ yang mengandung makna terpuji yaitu gembira senang dan bangganya orang-orang beriman dengan karunia dan rahmat-Nya. Kedua, farḥ yang mengandung makna tercela yaitu kegembiraan dan kesombongan orang-orang kafir dan orang-orang munafik.